Species identification and population dynamics of cuttlefish Sepia spp. (Mollusca: Cephalopoda) landed at Brondong Fishing Port, Lamongan, East Java, Indonesia - DADUK SETYOHADI; MUHAMMAD ARIF RAHMAN; LEDHYANE IKA HARLYAN; MIHROBI KHALWATU RIHMI (Society for Indonesian Biodiversity, 2024)
Abstract. Setyohadi D, Rahman MA, Harlyan LI, Rihmi MK. 2024. Species identification and population dynamics of cuttlefish Sepia spp. (Mollusca: Cephalopoda) landed at Brondong Fishing Port, Lamongan, East Java, Indonesia. Biodiversitas 25: 1359-1367. Cuttlefish (Sepia spp.) is one of Indonesia’s fisheries resources with high economic value. It is often caught in the northern Java waters, including Lamongan. As it is high value, cuttlefish resources should be managed to ensure sustainability. However, information on its biology and population dynamics is limited as the basis of fisheries management. This research aimed to identify species of cuttlefish and to estimate its biological aspects and population dynamics. Samples were randomly collected at Brondong Fishing Port from July to September 2022. The result indicated that there were two species of cuttlefish, Sepia aculeata (needle cuttlefish) and Sepia pharaonis (pharaoh cuttlefish), with a proportion of 57.1 and 42.9%, respectively. In addition, S. pharaonis was bigger and heavier than S. aculeata. The mean mantle length = 10.5 cm and weight = 166.6 g for S. aculeata, while S. pharaonis has mean mantle length = 11.4 cm and weight = 208.1 g, and both species have negative allometric growth patterns. Moreover, the asymptotic mantle length (L?) = 24.6 cm and 22.7 cm, growth rate (K) = 0.68 year-1 and 0.78 year-1, total mortality rate (Z) = 1.96 year-1 and 4.61 year-1, natural mortality rate (M) = 0.97 year-1 and 1.64 year-1, fishing mortality (F) = 0.99 year-1 and 2.97 year-1, and exploitation rate (E) = 0.51 year-1 and 0.65 year-1 for S. aculeta and S. pharaonis respectively. This finding might contribute to managing cuttlefish fishery in the north Java waters, especially in East Java.